Comparisons of the influence of vesicular-arbuscular mycorrhiza on the productivity of hedgerow woody legumes and cassava at the top and the base of a hillslope in alley cropping systems - Atayese, M.O.; Awotoye, O.O.; Osonubi, O.; Mulongoy, K. (1993)
We investigated the influence of vesicular-arbuscular mycorrhizal (VAM) inoculation on growth and nutrient relationships in two alley-cropping trials, one at the top and the other at the base of a hillslope. Each trial involved three woody hedgerow legumes with cassava (Manihot esculenta Crantz) as the sole intercrop. The hedgerow trees at the base of the slope showed greater survival and higher leaf dry weights than those at the top of the slope, although these parameters were not affected by VAM inoculation, either at the top or the base of the slope. In contrast to survival, the uptake of nutrients, particularly P and N, was higher for inoculated than uninoculated hedgerow trees, both at the top and at the base of slope. Increases in stem and leaf biomass and the uptake of nutrients by the trees were strongly correlated with increases in P uptake, indicating that the improvements were attributable to VAM inoculation. Cassava tuber yields at the base of the slope, from inoculated or uninoculated plants, were significantly greater than the corresponding cassava yields at the top of the slope. These increases at the base of the slope compared to the top of the slope were not attributed to available soil nutrients but to greater VAM spore density. Higher available soil moisture may have been another factor. Increasing the VAM spore density of effective mycorrhiza through proper agronomic practices at the top of a slope may bring about comparable yields on different parts of the slope.